Analysis, modelling and design of CLLC resonant converter for performance enhancement of fuel cell hybrid electric vehicle. (4th March 2022) - Mallikarjuna Reddy, Bandi; Samuel, Paulson
ABSTRACT: The deteriorating state of air and sound pollution over the last decade has its major stake in the astonishing growth of internal combustion engine-based automobile sector. Also, fossil fuel-based energy sources are not only severely impacting the ozone layer but also heading for a faster exhaustion. Simultaneously, the advances in power electronics have renewed the interest in electric vehicles. In this work, an efficient symmetric CLLC resonant dual active bridge isolated bidirectional dc/dc converter (RDAB-IBDC) and its modulation technique are proposed for the fuel cell hybrid electric vehicle. The performance comparison of the proposed converter and its modulation technique with generic dual active bridge isolated bidirectional dc/dc converter (GDAB-IBDC) is conducted in terms of switching loss reduction, efficiency, ripple analysis, cost and size. The comparison is also done between single phase shift (SPS) and flux link control (FLC) modulations. The simulation is carried out in PSCAD platform with 10 ohm constant resistive load. The RDAB-IBDC has excellent features compared to GDAB-IBDC in terms of higher switching frequency, less switching losses, higher efficiency, and more possibility of soft switching of both bridges with lesser circulating current.